2022
DOI: 10.3390/s22166233
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Measurements Using Electrical Impedance Spectroscopy to Monitor Fracture Healing

Abstract: There is an unmet need for improved, clinically relevant methods to longitudinally quantify bone healing during fracture care. Here we develop a smart bone plate to wirelessly monitor healing utilizing electrical impedance spectroscopy (EIS) to provide real-time data on tissue composition within the fracture callus. To validate our technology, we created a 1-mm rabbit tibial defect and fixed the bone with a standard veterinary plate modified with a custom-designed housing that included two impedance sensors ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…These applications include forces in joints, displacement during fracture healing, forces acting on dental implant prostheses, and bladder pressure ( Kim et al, 2012 ; D'Lima et al, 2013 ; Cho et al, 2014 ; Pelham et al, 2017 ). Fukase et al (2022) developed a smart bone plate to wirelessly monitor healing utilizing electrical impedance spectroscopy to provide real-time data on tissue composition within the fracture callus. The sensor is wireless and can take readings up to 3 m from the implanted bone for up to 8 weeks.…”
Section: Sensor Classificationmentioning
confidence: 99%
“…These applications include forces in joints, displacement during fracture healing, forces acting on dental implant prostheses, and bladder pressure ( Kim et al, 2012 ; D'Lima et al, 2013 ; Cho et al, 2014 ; Pelham et al, 2017 ). Fukase et al (2022) developed a smart bone plate to wirelessly monitor healing utilizing electrical impedance spectroscopy to provide real-time data on tissue composition within the fracture callus. The sensor is wireless and can take readings up to 3 m from the implanted bone for up to 8 weeks.…”
Section: Sensor Classificationmentioning
confidence: 99%
“…These findings suggest that the MEMS sensor can evaluate the present stage of fracture healing and be used to anticipate fracture healing. Numerous works have discussed wireless data and power transfer in other biomedical applications, such as smart contact lenses [36], monitoring fracture healing [37], and other applications.…”
Section: Related Workmentioning
confidence: 99%
“…Over time, changes in the resistive and capacitive properties occur as the bone heals resulting in change in the electrochemical nature of the tissue [ 23 ]. A limited number of studies have applied electrical impedance spectroscopy to in vivo animal bone fracture models [ 7 , 8 , 10 , 12 , 13 , 14 , 16 , 20 , 25 , 26 ]. All studies reported a consistently increased impedance over time across a range of frequencies, except one study [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…All studies reported a consistently increased impedance over time across a range of frequencies, except one study [ 7 ]. Of these, only two in vivo studies measured impedance at low frequencies [ 8 , 27 ]. The animals chosen for the studies varied between mice and rabbits.…”
Section: Introductionmentioning
confidence: 99%